Grafica Moderna 2 : Primavera 1971. (Campione d'Italia : Galleria Henze, 1971)
Alt, Otmar ; Amiet, Cuno ; Andersch, Gisela ; Antes, Horst ; Arp, Hans (Jean) ; Auberjonois, René ; Baj, Enrico ; Bargheer, Eduard ; Barlach, Ernst ; Baumeister, Willi ; Beckmann, Max ; Belling, Rudolf ; Bill, Max ; Bonnard, Pierre ; Brauer, Erich ; Bremer, Uwe ; Brodwolf, Jürgen ; Butler, Reg ; Campendonk, Heinrich ; Campigli, Massimo ; Chagall, Marc ; Chillida, Eduardo ; De Chirico, Giorgio ; Dali, Salvador ; Delvaux, Paul ; Dix, Otto ; Dufy, Jean ; Dunoyer de Segonzac, André ; Ernst, Max ; Feininger, Lyonel ; Francese, Franco ; Friedlaender, Johnny ; Fuchs, Ernst ; Grieshaber, HAP ; Grosz, George ; Guttuso, Renato ; Hässler, Uwe ; Hausner, Rudolf ; Hayter, Stanley William ; Hepworth, Barbara ; Hickert, Christian ; Hofer, Karl ; Hrdlicka, Alfred ; Hundertwasser ; Hüppi, Alfonso ; Itten, Johannes ; Jäger, Bernhard ; Janssen, Horst ; Kaus, Max ; Keckel, Erich ; Kirchner, Ernst Ludwig ; Klapheck, Konrad ; Klee, Paul ; Kokoschka, Oskar ; Kollwitz, Kathe ; Kruck, Christian ; Laurens, Henri ; Leger, Fernand ; Macke, August ; Manessier, Alfred ; Manzu, Giacomo ; Marini, Marino ; Matisse, Henri ; Meckseper, Friedrich ; Meidner, Ludwig ; Miro, Joan ; Moore, Henry ; Mueller, Otto ; Music, Zoran ; Nay, Ernst Wilhelm ; Nolde, Emil ; Pechstein, Max ; Purrmann, Hans ; Roeder, Emy ; Rohlfs, Christian ; Schmidt-Rottluff, Karl ; Severini, Gino ; Tappert, Georg ; Vallotton, Félix ; Vieira da Silva, Maria Elena ; Villon, Jacques ; de Vlaminck, Maurice ; Webels, Wilhelm ; Wunderlich, Paul ; Zadkine, Ossip
boek